(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The usefulness of wireless mesh networks has improved progressively over time due to their flexibility. A wireless mesh network, as its name implies, it is a network of interconnected wireless routers connected in a mesh topology, where data is transported via multiple transmission paths. An important component of an effective video security system is the implementation of the RSA algorithm to encrypt and decrypt the video. The ViLBaS concept is an existing concept, which detects all of the network’s nodes and confirms which of the network’s nodes is most impacted by the congestion. This concept is concerned with the OLSR protocol and how it is used to transport packets from the sender to the receiver. The system incorporates the ZRP protocol instead of the OLSR protocol in the proposed system. A similar idea can be implemented by utilizing a zone routing protocol. There are two protocols used in zone routing: the proactive protocol and the reactive protocol. We use "Proactive" techniques in which we send the packet directly to the receiver if both the sender and receiver are in the area defined. Reactive protocols will send the packet to the receiver if it is outside the reactive area. All quality-of-service parameters were assessed at the end.